Experiences and Contributions of CATIE to the Watershed Management in Tropical America - Jiménez-Otárola, Francisco (2019)
The contributions and experiences of CATIE in watershed management in Tropical America are discussed through its human capital formation programs, as well as the implementation of development and research programs and projects. The main experiences, contributions, and lessons learned are described, exemplified through the justification of the following aspects: the watershed as a unit of planning, management, and co-management of natural resources; the importance of approaching watershed management as a social construction; the conception of the basin as a system and water as the integrating resource; the adoption of the management of the basin as a shared responsibility of the stakeholders; the creation of basin committees as a mechanism for institutionalization, governance and sustainability of actions; the implementation of actions and processes with short, medium and long time horizons; the progression from management to co-management as part of the innovation to overcome limitations of the conventional watershed management approach; and the fact of having a tested methodological route for the watershed management process and the elaboration of management plans. Finally, some key elements for the management and co-management of watersheds are presented. These elements include the following: the intervention in micro-basins; the creation and strengthening of capacities; the importance of facilitating processes; the participatory action research associated with the adaptive management; the fact of taking advantage of learned experiences; the territorial ordering; financial mechanisms and the sustainability of actions.